2012
DOI: 10.1007/s10840-012-9715-0
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between fragmented QRS and response to cardiac resynchronization therapy

Abstract: Presence of dyssynchrony is necessary but not sufficient to select appropriate candidates for CRT. Presence of f-wQRS on baseline ECG may play a role in identifying patients who may not respond to CRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 33 publications
2
14
0
Order By: Relevance
“…This is similar to the study by Çelikyurt et al (23) which showed reverse remodeling after 6 months follow-up was significantly more common in patients with non-fragmented wide-QRS (35% vs. 89%, p=0.001). However in a study by Rickard et al (24) they found no difference in indices of LV remodeling or rates of all-cause mortality between patients with and without fQRS.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This is similar to the study by Çelikyurt et al (23) which showed reverse remodeling after 6 months follow-up was significantly more common in patients with non-fragmented wide-QRS (35% vs. 89%, p=0.001). However in a study by Rickard et al (24) they found no difference in indices of LV remodeling or rates of all-cause mortality between patients with and without fQRS.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, these factors, especially wide baseline QRS duration, which portend favorable outcomes, may overcome the negative influence that fQRS may have. As we see in Table 1 in our study similar to Çelikyurt et al (23) study, there was no significant difference between patients gender and baseline mean QRS duration in fQRS and non fQRS group. Our study showed; sensitivity, specificity, positive predictive value and negative predictive value of fQRS in predicting non-responsiveness to CRT were 91.3%, 47.3%, 80.7% and 69.2%, respectively.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Based on this evidence, current class I recommendations were restricted to patients with complete LBBB. However, recent studies showed that fragmented QRS complexes in the electrocardiograms of patients with nonischemic dilated cardiomyopathy and narrow QRS complexes are associated with significant intraventricular dyssynchrony [58,59], and other studies suggested that fragmented QRS complexes might be useful in predicting response to CRT [60,61]. Ongoing studies are investigating the possibility of maximizing CRT benefits by refining ECG selection criteria [62].…”
Section: Patient Selectionmentioning
confidence: 99%